Correction to: The Cedar Project: Using Indigenous-specific determinants of health to predict substance use among young pregnant-involved Indigenous women in Canada - Sana Z. Shahram; Joan L. Bottorff; Nelly D. Oelke; Leanne Dahlgren; Victoria Thomas; Patricia M. Spittal; For the Cedar Project Partnership (BMC, 2017)
Abstract After publication of the original article (1) it was noted that the title of this manuscript was incorrect. The title presently reads "The cedar project: using indigenous-specific determinants of health to predict substance use among young pregnant-involved aboriginal women" but should read "The Cedar Project: Using Indigenous-specific determinants of health to predict substance use among young pregnant-involved Indigenous women in Canada".